2011
DOI: 10.1186/1472-6963-11-157
|View full text |Cite
|
Sign up to set email alerts
|

Cost effectiveness of ulcerative colitis treatment in Germany: a comparison of two oral formulations of mesalazine

Abstract: BackgroundThe treatment of ulcerative colitis (UC) can place a substantial financial burden on healthcare systems. The anti-inflammatory compound 5-aminosalicylic acid (5-ASA; mesalazine) is the recommended first-line treatment for patients with UC. In this analysis, the incremental cost effectiveness ratio (ICER) of two oral formulations of 5-ASA (Mezavant® and Asacol®) is examined in the treatment of patients with mild-to-moderate, active UC in Germany.MethodsA Markov cohort model was developed to assess the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 24 publications
0
9
0
2
Order By: Relevance
“…Prenzler et al examined the annual direct health care cost for CD and UC patients in Germany based on the year 2007. They report-ed a cost of € 3767 for CD patients (68.5 % medication, 20.5 % inpatient treatment) and € 2478 for UC patients (74 % medication, 10 % inpatient treatment) [21]. As these data referred to a period 7 -9 years before our observation started and addressed all IBD patients instead of only IBD patients who started a therapy with biologics (as was the case in our study), the cost reported in this study cannot be compared to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Prenzler et al examined the annual direct health care cost for CD and UC patients in Germany based on the year 2007. They report-ed a cost of € 3767 for CD patients (68.5 % medication, 20.5 % inpatient treatment) and € 2478 for UC patients (74 % medication, 10 % inpatient treatment) [21]. As these data referred to a period 7 -9 years before our observation started and addressed all IBD patients instead of only IBD patients who started a therapy with biologics (as was the case in our study), the cost reported in this study cannot be compared to our results.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our data confirm the findings of Stark et al, 34 who concluded that the health care items that most influenced IBD-related health care costs were productivity losses and drug cost. Prenzler et al 35 examined the annual direct health care costs for patients with CD and patients with UC in Germany, based on the year 2007. They reported costs of V3767 for patients with CD (68.5% medication; 20.5% inpatient treatment) and V2478 for patients with UC (74% medication; 10% inpatient treatment).…”
Section: Hcru and Costsmentioning
confidence: 99%
“…Cuando analizamos las evaluaciones económicas de las distintas formulaciones de mesalazina procedentes de estudios internacionales, los trabajos publicados constatan un mayor coste-efectividad de las formulaciones evaluadas en el presente estudio (preparaciones gastrorresistentes de liberación prolongada y toma única) frente a otros tipos de formulaciones de 5-ASA 41,42 , pero no existen estudios que hayan comparado las distintas formulaciones dentro de este último grupo.…”
Section: Discussionunclassified